1990
DOI: 10.1007/3-540-53507-1_93
|View full text |Cite
|
Sign up to set email alerts
|

Foundations of canonical update support for closed database views

Abstract: A closed view of a database schema is one which is totally encapsulated. Insofar as the user is concerned, the view is the database schema. The rest of the database system is not visible through the view, and is is not required for complete use of the view. Similarly, the updates which may be effected through the view have their scope limited entirely to that view. In this paper, we lay the mathematical foundations for the systematic support of such views. The proper context is shown to be that of update trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…Bidirectional transformation [10], originating from the view-updating technique in the database community [3,5,11,12,16], involves a pair of transformations between a source and its view: the first transformation, called forward transformation, maps sources to views and is used to reflect changes in a source in its view. The second transformation, called backward transformation, maps views to sources and is used to reflect changes in a view in its source.…”
Section: Bidirectional Transformationmentioning
confidence: 99%
See 2 more Smart Citations
“…Bidirectional transformation [10], originating from the view-updating technique in the database community [3,5,11,12,16], involves a pair of transformations between a source and its view: the first transformation, called forward transformation, maps sources to views and is used to reflect changes in a source in its view. The second transformation, called backward transformation, maps views to sources and is used to reflect changes in a view in its source.…”
Section: Bidirectional Transformationmentioning
confidence: 99%
“…Our design of the Web site maintenance system, Vu-X, based on bidirectional transformation was greatly inspired by pioneering work [10,4] on data synchronization based on bidirectional transformation, which originated from work on view updating [3,5,11,12,16] in the database community, where modifications to view could be reflected back to the original database. We borrowed this technique to enable Web site maintenance with one significant extension: editing operations can not only modify the view but also the transformation code, which has not been exploited before.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…While here we study properties of decompositions in which the component schemata have nontrivial constraints connecting them, [17] examines direct decompositions, in which all views are independent. The paper [18] also deals with decompositions in a general context, but focuses upon the problem of updates rather than schema desirability. This paper began as the full version of the conference paper [19].…”
Section: Relationship To Other Workmentioning
confidence: 99%
“…14 and Thm. 14], although a specific characterization in terms of the meet is first presented in [12] and refined greatly in [13], where it is also shown that for the case of projections of relational schemata constrained by usual database dependencies, state invariance is obtained precisely in the case that a cover of the dependencies of the main schema embed into the two views [13,Prop. 2.17].…”
Section: Introductionmentioning
confidence: 99%